The Influence of English Trainer Competence on the English Language Proficiency of Trainees in Community Learning Centers Across Banyuwangi Regency - Alvianita Nur Wahyuni; Ach Rasyad; Edi Widianto (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This study aims to determine the influence of tutor competence on the English language proficiency of training participants. The researcher applied a quantitative correlational research design and used simple linear regression analysis. The population studied was all English language training participants in the Community Learning Center (CLC) of Banyuwangi Regency, with a total of 10 CLCs that provide English language training. The research was conducted over 5 months, from August to December 2021, with a sample size of 33 participants from 10 CLCs. Proportional random sampling technique was used to obtain the sample. Data was collected through the administration of a questionnaire as the primary method. The questionnaire was distributed to the 10 CLCs identified as the sample. The results showed that the tutor competence in teaching English has a score of 83.4%, indicating excellent competence, while the English language proficiency of the participants has a score of 65.4%, indicating moderate proficiency. The influence of tutor competence has a value of 0.405, which has a "moderately strong" coefficient interpretation, indicating a significant influence between tutor competence and English language proficiency. Additionally, the significance between the variables (X) Tutor Competence and (Y) English Language Proficiency had a sig value of 0.019, which indicates that if the significant value (0.019) < alpha (0.05), then Ho is rejected and Ha is accepted, which means there is an influence between tutor competence and the English language proficiency of training participants.